Discomfort, expectations, and experiences during treatment of large overjet with Andresen Activator or Prefabricated Functional Appliance: a questionnaire survey. (3rd April 2017) - Čirgić, Emina; Kjellberg, Heidrun; Hansen, Ken
Abstract: Background: The purpose of this study was to investigate the amount of functional and social discomfort experienced after 1 and 6 months of appliance wear, comparing a slightly modified Andresen Activator (AA) and a Prefabricated Functional Appliance (PFA). Methods: Ninety-seven patients randomly selected by lottery in an AA (40 subjects), and a PFA (57 subjects) group, with an Angle Class II, Division 1 malocclusion, were eligible for the study. One month and 6 months after start of treatment, a questionnaire, addressing discomfort, perception of treatment need and outcome, was used. Results: The response rate was 69% after 1 month, and 45% after 6 months. The most common discomfort reported was the 'appliance falling out during sleep' followed by 'difficulties in remembering it'. The only difference was for pain, which was experienced more extensively in the AA group after 1 month of treatment. The dentist appeared to have the greatest impact on the decision to initiate treatment. Teasing, because of appearance, occurred in 13% of the cases. Conclusions: No difference could be seen between groups for the experience of functional or social discomfort after 6 months of appliance use. Adequate time should be allowed for clarifying treatment difficulties, using treatment need as motivation. Practical implications: The PFA eliminates the need for taking impressions. Furthermore, it can be economically advantageous to both patients and clinicians.